A hybrid content based image retrieval system using log-gabor filter banks - D. Madhavi; Khwaja Muinuddin Chisti Mohammed; N. Jyothi; M. Ramesh Patnaik (Institute of Advanced Engineering and Science, 2019)
In this paper, a new efficient image retrieval system using sequential process of three stages with filtering technique for the feature selection is proposed. In the first stage the color features are extracted using color histogram method and in the second stage the texture features are obtained using log-Gabor filters and in the third stage shape features are extracted using shape descriptors using polygonal fitting algorithm. The proposed log-Gabor filter in the second stage has advantages of retrieving images over regular Gabor filter for texture. It provides better representation of the images. Experimental evaluation of the proposed system shows improved performance in retrieval as compared to other existing systems in terms of average precision and average recall.